Pengaruh Aplikasi Pupuk Organik Cair Urine Sapi dan Trichoderma sp. Terhadap Beberapa Sifat Kimia Tanah Ultisol dan Hubungannya Terhadap Hasil Kedelai Edamame - Radina, Gusti Nurlaili; Gazali, Akhmad; Aziza, Noor Laili (Universitas Lambung Mangkurat, 2023)
Edamame is a type of soybean (Glycine max (L) Merr.) which has an average production of 3.5 t.ha-1 higher than the production of ordinary soybeans, so it requires a large enough basic fertilizer requirement. Some important elements in total nutrient balance are C-Organic, total N and C/N. Liquid fertilizer is more easily absorbed by plants because the nutrients contained have been decomposed. Organic fertilizers are fertilizers that play a role in increasing the biological, chemical, and physical activities of the soil. While Trichoderma sp. is a soil saprophytic fungus that produces organic compounds in the decomposition process of various organic materials. The aim of the study was to determine the effect of giving cow urine POC and Trichoderma sp. on the content of C-organic, total N, and C/N as well as soybean yield on ultisol soil, knowing the most influential concentration and the relationship between C-Organic, total N, and C/N on edamame soybean production. The study was carried out at the Experimental Field, Department of Agroecotechnology, from July – October 2019. The study used a combination randomized block design (RAK) of cow urine POC and Trichoderma sp. There were 9 treatment combinations with 3 replications, so that 27 experimental units were obtained. Observation parameters were the effect of combination on C-organic content (%), total N (%), C/N, number of pods (fruit), and wet weight per plot (grams). The best combination of treatment was cow urine POC treatment 0 ml.l-1 water + Trichoderma sp. 40 ml.plant-1.